1996
DOI: 10.1136/gut.39.2.342
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal adenoma-carcinoma sequence.

Abstract: Colorectal adenoma-carcinoma sequence EDITOR,-I read with interest the article by Fernandez-Banares et al (Gut 1996; 38: 254-9). These authors demonstrated novel significant differences in tissue fatty acid profiles when they compared diseased and paired normal mucosa of adenoma and carcinoma patients. My one concern about this study is the author's comparison between tissue fatty acid profiles with plasma fatty acid concentrations that only reflect recent intake and give no information on the longterm dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Colorectal cancer is the fourth most frequent cancer and has a high mortality worldwide. Colorectal cancers, according to the adenoma–carcinoma sequence theory, arise primarily in a setting where a multistep carcinogenesis event progresses from colorectal adenoma with a low grade of dysplasia to high dysplasia and, finally, to carcinoma 1 . Thus, colorectal adenoma has been recognized as the main precancerous lesion for most colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer is the fourth most frequent cancer and has a high mortality worldwide. Colorectal cancers, according to the adenoma–carcinoma sequence theory, arise primarily in a setting where a multistep carcinogenesis event progresses from colorectal adenoma with a low grade of dysplasia to high dysplasia and, finally, to carcinoma 1 . Thus, colorectal adenoma has been recognized as the main precancerous lesion for most colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, colorectal adenoma has been recognized as the main precancerous lesion for most colorectal cancers. Although many molecular and genetic alterations involved in this sequence have been identified, 1 the exact mechanisms of the adenoma–carcinoma transition are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…According to the adenoma-carcinoma sequence hypothesis, most sporadic CRCs develop primarily from a pre-existing adenoma in a setting where a multistep molecular and histological carcinogenesis event progresses to a carcinoma (1,2). The transition from an adenoma to a CRC may take many years and can inevitably result in a series of changes that include altered cytokine secretion and immune cell function in the tumor microenvironment (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The important fundamental concept of colorectal cancer development is the "adenoma-carcinoma sequence." This is the carcinogenesis pathway of normal mucosa involving accumulation of genetic mutations and epigenetic changes, transformation to an adenomatous colorectal polyp, and eventually transformation to colorectal cancer, in a stepwise progression (28,29). Many studies have shown that endoscopic removal of colorectal polyps prevents colorectal cancer, and their results support the sequence pathway (30,31).…”
Section: Discussionmentioning
confidence: 95%